“colombie, années 40: de la frustration à l’imagination” (2013)
This article of Jacques Gilard (1943-2008) remained unpublishedsince the death of its author and discusses thecentral ideas of literary trends in the political context of1940s Colombia. The main characters of this reflectionare Gabriel García Marquez and Alvaro Mutis, with referencesto the political and literrty stances of importantColombian intellectual and writers as Tomas VargasOsorio, Eduardo Zalamea Borda, Jorge Gaitán Duran,German Arciniegas and Hernando Téllez.